Analisis Kevalidan Modul Pembelajaran Berbantuan Quick Response Code pada Materi Gelombang Mekanik SMA Negeri 1 Muara Beliti - Sarmila, Eci; Gumay, Ovilia Putri Utami; Lovisia, Endang (ANTHOR: Education and Learning Journal, 2023)
The purpose of this study was to determine the quality of the development of quick response code-assisted learning modules on mechanical wave material in terms of validity. This research is a research and development R&D (Research andDevelopment) using a 4D development model which has a development stage consisting of 4 stages of development, namely: Define (defining), Design (planning), Development (development), and Dissemination (deployment). Data collectiontechniques in the form of a module validity questionnaire. The subject of this research is class XI SMA Negeri 1 Muara Beliti. The validity assessment obtained was material validation = 43, media validation = 34, and language validation = 20 with an average score of 0,87 in the very valid category after the quick response code-assisted learning module was validated by experts. thus it can be concluded that the quick response code learning module is valid, so this learning module can be used in learning.